Objects of worship in South Asian religions forms, practices and meanings - Jacobsen, Knut A. 1956-; Aktor, Mikael; Myrvold, Kristina 1972- (Routledge Studies in Asian Religion and Philosophy, 2014)
"Objects of worship are an aspect of the material dimension of lived religion in South Asia. The omnipresence of these objects and their use is a theme which cuts across the religious traditions in the pluralistic religious culture of the region. Divine power becomes manifest in the objects and for the devotees they may represent power regardless of religious identity. This book looks at how these objects dominate the religious landscape of South Asia, and how they are of significance not just to the religious but also the social life of the region. It shows how these objects are shaped by traditions of religious aesthetics and conceptual devices woven into webs of religious and social meaning and demonstrates how the objects have a living relationship with those who use them. It discusses how devotees relate to such objects in a number of ways, and that although they belong to various traditions, objects may attract people from different communities and can be contested. By analysing the specific qualities that make objects eligible for becoming living objects of worship, and demonstrating how the objects have a living relationship with those who use them, the book contributes to an understanding of the central significance of these objects in the religious and social life of South Asia. It will be of interest to students and scholars of Asian Religion, South Asian Studies, Philosophy and Culture and Society"..